A Counterexample to Variabilism. - CAPRARU, MIHNEA D. I. (Analysis, 2016)
The article discusses the argue on variabilism and its counterexamples. Topics mentioned include the view of professor Sam Cumming on understanding the proper names as analogues of natural language, the maintain on the function of proper names as bound variables, and the two rescue approach by variabilist through counter example claim and modifying the Binding Theory of grammar.